1995
DOI: 10.1113/jphysiol.1995.sp020789
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide hyperpolarizes rabbit mesenteric arteries via ATP‐sensitive potassium channels.

Abstract: 1. Nitric oxide (NO) relaxes vascular smooth muscle (VSM) by mechanisms which are not fully understood. One possibility is that NO hyperpolarizes membranes, thereby diminishing Ca2+ entry through voltage-dependent Ca2+ channels. In the current study, the effects of NO on membrane potential of rabbit mesenteric arteries were recorded using intracellular microelectrodes. 2. NO, released by 3-morpholinosydnonimine (SIN-1, 3/M), reversibly hyperpolarized arteries by -9-5 + 4 0 mV (means + S.D., n = 97) from a rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
190
5
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(212 citation statements)
references
References 38 publications
16
190
5
1
Order By: Relevance
“…In vascular smooth muscle, treatment with isosorbide dinitrate, a stimulator of soluble guanylyl cyclase, resulted in the activation of K ATP and this effect was blocked by methylene blue, an inhibitor of guanylyl cyclase (Kubo et al 1994). Similarly, treatment of mesenteric arteries with nitric oxide or lemakalim (a K ATP activator) hyperpolarized the muscle membrane (Murphy and Brayden, 1995). This hyperpolarization was suppressed by either oxyhemoglobin (a nitric oxide scavenger) or by glibenclamide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vascular smooth muscle, treatment with isosorbide dinitrate, a stimulator of soluble guanylyl cyclase, resulted in the activation of K ATP and this effect was blocked by methylene blue, an inhibitor of guanylyl cyclase (Kubo et al 1994). Similarly, treatment of mesenteric arteries with nitric oxide or lemakalim (a K ATP activator) hyperpolarized the muscle membrane (Murphy and Brayden, 1995). This hyperpolarization was suppressed by either oxyhemoglobin (a nitric oxide scavenger) or by glibenclamide.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these reports indicate a linkage between the cyclic GMP signalling pathway and activation of K ATP (Lazaro-Ibanez et al 2001;Soares and Duarte 2001;Sachs et al, 2004). Indeed, studies of other cellular systems have demonstrated that cyclic GMP can lead to the activation of K ATP (Kubo et al 1994;Murphy and Brayden, 1995;Armstead 1997Armstead , 1998Schwingshackl et al 2002). These behavioral measures of the antinociceptive actions of K ATP suggest that this channel may play an important role in reversing or antagonizing the sensitizing effects of a variety of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…The K ATP channel opening action of nicorandil, in common with other K ATP channel openers, is usually thought to occur as a direct action on the channel (see Quayle et al, 1997 for review). It is also possible, however, that channel activation occurs through activation of GC as a result of the nitrovasodilator action of nicorandil, since nitric oxide has been reported to cause glibenclamide-sensitive hyperpolarization of rat and rabbit mesenteric arteries (Garland & McPherson, 1992;Murphy & Brayden, 1995) and isosorbide dinitrate, atrial natriuretic peptide, and 8-bromo cyclic GMP can activate K ATP channels in cultured rat aortic cells (Kubo et al, 1994). Finally, on the basis of experiments using myography and membrane potential recording in rat mesenteric artery, Fujiwara & Angus (1996) have recently suggested that nicorandil might have a third mechanism of action, causing inhibition of nifedipinesensitive Ca 2+ channels directly.…”
Section: Introductionmentioning
confidence: 99%
“…NO can also increase the gastric blood fl ow by activation of ATP-sensitive potassium channels (K ATP ) (Murphy and Brayden, 1995). To evaluate the role of K ATP in the gastroprotection by NvEtOH, a pretreatment with glibenclamide (5 mg/ kg BW), a well-known blocker of these channels, was performed in the ethanol-induced gastric lesion model.…”
Section: Discussionmentioning
confidence: 99%